2009
DOI: 10.1080/13545700802712497
|View full text |Cite
|
Sign up to set email alerts
|

Do Gender Disparities in Employment Increase Profitability? Evidence from the United States

Abstract: This paper investigates whether the contribution of the declining share of wages in national income to the upswing in profitability between 1982 and 1997 in the United States was aided by the growing incorporation of women into employment. The analysis finds that women helped moderate the decline in the aggregate wage share. The reduction in gender pay disparity overwhelmed the negative effect of women's growing share of market work on the wage share. However, in (one-digit) sectors where wage shares fell, wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…We aggregate sectors to make our results comparable to those in Zacharias and Mahoney (2009), where it was found that, in the US, structural change contributed to the wage share dynamics only by 10 percent between 1982 and 1997. Table 4 shows that it had a much greater role in Italy from 1994 to 2005, when the economy was shifting from sectors where income distribution had a positive contribution to the aggregate wage share (especially manufacturing and trade) to sectors with negative contributions (especially financial intermediation).…”
Section: Changes In the Distribution And Structure Of Italian Economymentioning
confidence: 54%
See 4 more Smart Citations
“…We aggregate sectors to make our results comparable to those in Zacharias and Mahoney (2009), where it was found that, in the US, structural change contributed to the wage share dynamics only by 10 percent between 1982 and 1997. Table 4 shows that it had a much greater role in Italy from 1994 to 2005, when the economy was shifting from sectors where income distribution had a positive contribution to the aggregate wage share (especially manufacturing and trade) to sectors with negative contributions (especially financial intermediation).…”
Section: Changes In the Distribution And Structure Of Italian Economymentioning
confidence: 54%
“…Therefore, the Italian workforce also experienced an increasing feminization. Zacharias and Mahoney (2009) phenomenon in the US, including an attempt to defend family living standards from declines in men's compensation, social and educational factors changing women's preferences, declines in fertility and marriage rates, and increases in the rate of divorces. Italian society went through similar changes in the past decades.…”
Section: Gender Aspects Of Employment and Functional Distributionmentioning
confidence: 99%
See 3 more Smart Citations